The 2013-15 Decline in NAEP Mathematics: What it Teaches Us about NAEP and the Common Core. Issue 4 (2nd October 2021) - Camilli, Gregory
ABSTRACT: After 25 years with small to moderate gains in performance in mathematics, scores on the National Assessment of Educational Progress (NAEP) main assessment declined between 2013 and 2015 in Grades 4 and 8. Previous research has suggested the decline may be linked to the implementation of the Common Core state standards. In this article, the decline in the NAEP composite score is shown to be driven primarily by losses in the content strands of Geometry and of Data Analysis, Statistics, and Probability. A gain in fractions achievement is also evident in an item-level examination of the NAEP results, but not in reported NAEP scores. These effects are discussed with respect to the CCSS, the rationale for evaluating national progress, and a potential redesign of the NAEP assessment.